Brain Plasticity and Cell Competition: Immediate Early Genes Are the Focus - Pavel P. Tregub; Yulia K. Komleva; Maria V. Kukla; Anton S. Averchuk; Anna S. Vetchinova; Natalia A. Rozanova; Sergey N. Illarioshkin; Alla B. Salmina (Cells)
Brain plasticity is at the basis of many cognitive functions, including learning and memory. It includes several mechanisms of synaptic and extrasynaptic changes, neurogenesis, and the formation and elimination of synapses. The plasticity of synaptic transmission involves the expression of immediate early genes (IEGs) that regulate neuronal activity, thereby supporting learning and memory. In addition, IEGs are involved in the regulation of brain cells’ metabolism, proliferation, and survival, in the establishment of multicellular ensembles, and, presumably, in cell competition in the tissue. In this review, we analyze the current understanding of the role of IEGs (c-Fos, c-Myc, Arg3.1/Arc) in controlling brain plasticity in physiological and pathological conditions, including brain aging and neurodegeneration. This work might inspire new gene therapy strategies targeting IEGs to regulate synaptic plasticity, and potentially prevent or mitigate neurodegenerative diseases.